1995
DOI: 10.1254/jjp.69.435
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of KW-4679, an Antiallergic Drug, on Experimental Allergic Rhinitis in Guinea Pigs: Effects on Nasal Blockage

Abstract: ABSTRACT-Weinvestigated the effect of KW-4679 (Z-11-(dimethylaminopropyliden)-6,11-dihydrodibenzoxepin-2-acetic acid hydrochloride), an antiallergic agent, on the nasal blockage induced by antigen challenge into the nostrils of actively sensitized guinea pigs. The change of the nasal cavity volume caused by nasal mucosal swelling after antigen challenge was measured by acoustic rhinometry. Oral administration of KW-4679 (0.01-10 mg/kg) significantly inhibited the decrease in the nasal cavity volume at 10 min, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…We confirmed that olopatadine significantly inhibited the sneeze and nasal rubbing responses in the actively sensitized guinea pig (T. Kaise et al, unpublished data) as well as in the passively sensitized animal (7). In addition, we have reported that chlorpheniramine, a classic histamine H1-antagonist, prominently inhibited the sneeze and nasal rubbing responses in the actively sensitized animal, while pranlukast, a LT-receptor antagonist, and seratrodast failed to inhibit these responses (11).…”
supporting
confidence: 74%
See 3 more Smart Citations
“…We confirmed that olopatadine significantly inhibited the sneeze and nasal rubbing responses in the actively sensitized guinea pig (T. Kaise et al, unpublished data) as well as in the passively sensitized animal (7). In addition, we have reported that chlorpheniramine, a classic histamine H1-antagonist, prominently inhibited the sneeze and nasal rubbing responses in the actively sensitized animal, while pranlukast, a LT-receptor antagonist, and seratrodast failed to inhibit these responses (11).…”
supporting
confidence: 74%
“…The previous in vitro studies demonstrated that olopatadine inhibited the mediator release from several inflammatory cells (5,6). Kaise et al reported that olopatadine inhibited the sneeze and nasal rubbing responses and the nasal blockage caused by antigen challenge in sensitized guinea pigs (7,8). Moreover, olopatadine has been shown to be useful for the treatment of allergic rhinitis in human patients (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In sensitized guinea pigs, LY303870 or SR48968 was intravenously administered 30 min before, and CGRP(8 -37) was intravenously given 2 min before the intranasal antigen challenge. The nasal cavity volume was measured before and until 6 h after the challenge, since our previous study demonstrated that the decreases in the nasal cavity volume developed till 6 h after the antigen challenge in sensitized guinea pigs (17).…”
Section: Effects Of Antagonists Against Neuropeptides On Nasal Obstrumentioning
confidence: 99%